Karakteristik Morfologi Ikan Gelodok (Periophthalmus chrysospilos) Di Area Hutan Mangrove Mundu, Kabupaten Cirebon - Muhimatul Umami (Universitas Nusantara PGRI Kediri, 2022)
Gelodok or mudskipper fish is a type of Gobiidae family that are dominant fishes in the mangrove forest, one of them Mangrove forest in the Coastal Cirebon. This study aims to identify species of mudskipper fish in the coastal Cirebon based on morphometric and meristic characters. This research method using purposive sampling, with two areas: Mundu Pesisir and Kanci river estuary. The mudskipper are collected when low tide use manually collection and uses the net fishing. The collected samples were then identified based on 17 morphometric measurment and 10 meristic characters. The identification results were compared with key identification books.The results shown that Periophthalmus chrysospilos has an elongated body shape with a rounded tail, brown body colour with golden spots, the dorsal fin has a black upper part while the dorsal fin has a golden spot accompanied by a black line, has eyes on the top of the head that can rotate around, inferior mouth. Body length 6.8–10.6 cm.